2015
DOI: 10.1186/s12879-015-1035-4
|View full text |Cite
|
Sign up to set email alerts
|

Divergent cerebrospinal fluid cytokine network induced by non-viral and different viral infections on the central nervous system

Abstract: BackgroundMeningoencephalitis is one of the most common disorders of the central nervous system (CNS) worldwide. Viral meningoencephalitis differs from bacterial meningitis in several aspects. In some developing countries, bacterial meningitis has appropriate clinical management and chemotherapy is available. Virus-associated and virus not detected meningoencephalitis are treatable, however, they may cause death in a few cases. The knowledge of how mediators of inflammation can induce disease would contribute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Even cytokines seemed to have the ability to distinguish enterovirus infection from other viruses. Enterovirus meningoencephalitis group showed higher level of CSF IL‐6, TNF, and IL‐17 when compared to arbovirus, lentivirus, and herpes groups . While compared to patients with human parechovirus meningitis, CSF levels of the majority cytokines were still significantly higher in patients with EVM …”
Section: Discussionmentioning
confidence: 90%
“…Even cytokines seemed to have the ability to distinguish enterovirus infection from other viruses. Enterovirus meningoencephalitis group showed higher level of CSF IL‐6, TNF, and IL‐17 when compared to arbovirus, lentivirus, and herpes groups . While compared to patients with human parechovirus meningitis, CSF levels of the majority cytokines were still significantly higher in patients with EVM …”
Section: Discussionmentioning
confidence: 90%
“…CSF CXCL8, CXCL9, and CXCL10 are elevated in herpes simplex herpes simplex virus (HSV) 1 encephalitis and HSV2 meningitis, whereas CXCL11 and CCL8 are elevated in HSV2 meningitis alone ( 151 ). Among viral CNS meningoencephalitides, enterovirus and lentivirus have comparably higher CSF IL-12 and IFN-γ concentrations, whereas arbovirus is associated with lower CSF cytokine concentrations than other viral etiologies ( 168 ). In mumps meningitis in children, the concentrations of CSF CXCL8, IL-10, IL-12, IL-13, and IFN-γ were higher than in other viral meningitides ( 153 ).…”
Section: Comparison Of Csf Ck/cytokine Immunomarker Profiles In Humanmentioning
confidence: 99%
“…Due to the ability of the virus to spread and infect other host organs, the initial silent infection may quickly develop more negative effects. [57][58][59][60]. Further investigations showed that even IL-6 and TNF-α, which are usually more linked to bacterial meningitis, are present in the CNS during an aseptic viral meningitis [61].…”
Section: Life Cycle Of Echovirus 30mentioning
confidence: 99%